2014
DOI: 10.16943/ptinsa/2014/v80i2/3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Insect Pests by Microorganisms

Abstract: Insects, like other organisms, are susceptible to a variety of diseases caused by bacteria, viruses, fungi and protozoans, and these pathogens are exploited for biological control of insect pests through introductory or inundative applications. Microbial pathogens of insects are intensively investigated to develop environmental friendly pest management strategies in agriculture and forestry. In this paper, the scope for utilization of insect pathogens in pest management in the world and India is reviewed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Also, El-Husseini (2006) showed that the entomopathogenic bacteria an important factor of the natural mortality to insect pests. Ramanujam et al (2014) reported that the main advantages of these biocontrol agents are their specificity to target pests, safety to the nontarget organism. They do not cause ill effects on environment and human health and can be used against pests which develop resistance to the conventional insecticides.…”
Section: Monitoring the Natural Mortality Of Cassida Vittata Adults Wmentioning
confidence: 99%
“…Also, El-Husseini (2006) showed that the entomopathogenic bacteria an important factor of the natural mortality to insect pests. Ramanujam et al (2014) reported that the main advantages of these biocontrol agents are their specificity to target pests, safety to the nontarget organism. They do not cause ill effects on environment and human health and can be used against pests which develop resistance to the conventional insecticides.…”
Section: Monitoring the Natural Mortality Of Cassida Vittata Adults Wmentioning
confidence: 99%
“…The broken line inset box indicates the common microbial determinants of both insecticidal and nematicide capacity. Duarte et al, 2016;Gonzalez et al, 2016;Khan et al, 2016;Malekan et al, 2015;Mascarin and Jaronski, 2016;QuesadaMoraga et al, 2006;Ramanujam et al, 2014;Safavi, 2013;Xu et al, 2009 Metarhizium anisopliae Haase et al, 2015;Monteiro et al, 2012;Ramanujam et al, 2014;Yang et al, 2012HezeSNPV Helicoverpa zea Gemstar, HzNPV CCAB Haase et al, 2015Lacey et al, 2015;Rowley et al, 2011 MabrNPV Mamestra brassicae;H. armigera;S.…”
Section: Figmentioning
confidence: 99%
“…Hence, controlling stored product insect pests may be most beneficial in long-term storage since such entomopathogenic protozoans produce slow-acting chronic infection. Furthermore, they may cause a reduction in host vitality, feeding, fecundity, longevity, and survivorship (McLaughlin, 1971;Khan and Selman, 1989;Flinn and Schöller, 2012;Ramanujam et al, 2014). Weiser et al (1976) recorded promising examples for certain entomopathogenic protozoans that cause reductions in storage insect pests.…”
Section: Introductionmentioning
confidence: 99%